The Effect of Earnings Persistence and Leverage on Earnings Response Coefficient with Good Corporate Governance as Moderator - Adyani, Ni Putu Hena; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2025)
This study aims to determine the effect of earnings persistence and leverage on earnings response coefficient with good corporate governance as moderation. The population of this study are IDX80 companies listed on the Indonesia Stock Exchange for the period 2019-2023. The sample was selected using purposive sampling technique and obtained a sample of 120 observations. The data analysis technique was carried out by conducting the MRA test with SPSS software.  The results of this study indicate that earnings persistence has a positive effect on ERC, the higher the earnings persistence generated by the company, the higher the ERC of the company. Leverage has a negative effect on ERC, when the company has a high level of leverage it can reduce investor interest in investing, so that ERC will decrease. This study also found that GCG was able to moderate the effect of earnings persistence and leverage on ERC.  Keywords: earnings response coefficient; earnings persistence; leverage; good corporate governance.